Tobacco use prevalence and correlates among adolescents in a clinician initiated tobacco prevention trial in California, USA. Issue 3 (June 1996) - Hovell, M F; Slymen, D J; Keating, K J; Jones, J A; Burkham-Kreitner, S; Hofstetter, C R; Noel, D; Rubin, B
Abstract : OBJECTIVES: Baseline data for the clinician initiated, tobacco prevention trial, the first non-school based clinician mediated tobacco prevention study, were used to explore the degree to which young people receiving orthodontic treatment use tobacco and the differences in use rates between national, California, and patient samples. Correlates of tobacco use were identified and these correlates were contrasted with findings from the published reports. DESIGN AND SETTING: A 26 item telephone survey assessed demographic information, tobacco use, selected health related behaviours, and variables based on social learning theory. The study was conducted among 11 to 18 year old orthodontic patients from San Diego, Orange, Riverside, San Bernardino, and Los Angeles Counties, California, USA. PARTICIPANTS: Of the 17925 patients who were eligible, 16915 (> 94%) completed the survey. MEASUREMENTS AND MAIN RESULTS: Multivariate analyses were conducted using a logistic mixed effects model. Although the 30 day prevalence rate of tobacco use (6%, n = 1010) proved lower than California and national samples, the rates for the age, gender, and race ethnicity subgroups showed trends similar to those seen in California and national samples. Ten variables were significantly associated with tobacco use (p < 0.05), including 30 day alcohol use (OR = 7.88), age (OR = 1.32), and living with a tobacco user (OR = 1.72). CONCLUSIONS: Because 6% of orthodontic patients use tobacco, interventions are warranted to reach the health "Objectives for the Nation". Patterns of correlates of tobacco use were essentially the same for orthodontic patients, California, and national samples, suggesting that these associations are generalisable.